Case reportPosttraumatic infrarenal abdominal aortic pseudoaneurysm treated with bifurcated endovascular graft stent - Oner, Ender; Erkanli, Korhan; Akturk, Ibrahim Faruk; Aydin, Unal; Akinci, Okan; YIldIrIm, AydIn (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Posttraumatic infrarenal aortic pseudoaneurysms are rare and potentially lethal lesions. We report the case of a 32-year-old man presenting with infrarenal aortic pseudoaneurysm eight months after being stabbed in the back and right flank. His pseudoaneurysm was close to the iliac bifurcation, so we decided to deploy a bifurcated endovascular graft stent, the TriVascular Ovation endovascular stent. Imaging one month after the procedure revealed no endoleak and slight shrinkage of the pseudoaneurysm.